2020
DOI: 10.1101/2020.05.28.119297
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Keratin 19 maintains E-cadherin localization at the cell surface and stabilizes cell-cell adhesion of MCF7 cells

Abstract: A cytoskeletal protein keratin 19 (K19) is highly expressed in breast cancer but its effects on breast cancer cell mechanics are unclear. Using KRT19 knockout (KO) cells and cells where K19 expression was rescued, we found that K19 is required to maintain rounded epithelial-like shape and tight cell-cell adhesion of MCF7 cells. A loss of K19 resulted in a lower level of plakoglobin and internalization of E-cadherin in early and recycling endosomes. Inhibiting internalization restored cell-cell adhesion of KRT1… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 67 publications
(84 reference statements)
0
1
0
Order By: Relevance
“…This suggested that K19 has little to no effect on the mechanism of nucleic acid recognition by HNRNPK and that changes in HNRNPK gene regulatory activity were most likely due to changes in its localization. Indeed, keratins regulate the localization of proteins in the cytoplasm to impact cellular and physiological processes including cell cycle, translation, cell-cell adhesion (25,(34)(35)(36). Our data show that in the presence of K19, HNRNPK increases the abundance of target mRNAs in the cytoplasm, very likely by increasing their stability and possibly through competition with other RBPs (37).…”
Section: K19 and Hnrnpk Co-regulate P53 Signaling Pathwaymentioning
confidence: 81%
“…This suggested that K19 has little to no effect on the mechanism of nucleic acid recognition by HNRNPK and that changes in HNRNPK gene regulatory activity were most likely due to changes in its localization. Indeed, keratins regulate the localization of proteins in the cytoplasm to impact cellular and physiological processes including cell cycle, translation, cell-cell adhesion (25,(34)(35)(36). Our data show that in the presence of K19, HNRNPK increases the abundance of target mRNAs in the cytoplasm, very likely by increasing their stability and possibly through competition with other RBPs (37).…”
Section: K19 and Hnrnpk Co-regulate P53 Signaling Pathwaymentioning
confidence: 81%